2021
DOI: 10.3390/biom11050706
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning Azelnidipine as a Dual Inhibitor Targeting CD47/SIRPα and TIGIT/PVR Pathways for Cancer Immuno-Therapy

Abstract: Strategies boosting both innate and adaptive immunity have great application prospects in cancer immunotherapy. Antibodies dual blocking the innate checkpoint CD47 and adaptive checkpoint PD-L1 or TIGIT could achieve durable anti-tumor effects. However, a small molecule dual blockade of CD47/SIRPα and TIGIT/PVR pathways has not been investigated. Here, an elevated expression of CD47 and PVR was observed in tumor tissues and cell lines analyzed with the GEO datasets and by flow cytometry, respectively. Compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Azelnidipine is a long-acting third-generation dihydropyridine calcium channel blocker that has been approved for the treatment of hypertension. However, using the molecular operating environment (MOE) by blocking and MST binding assays, molecular docking and structural analysis of CD172a and CD112 have indicated azelnidipine’s potential relevance in cancer immunotherapy ( 171 ). Azelnidipine inhibits the innate checkpoint CD47/CD172a and the adaptive checkpoint TIGIT–CD112 pathways and has anti-cancer effects by increasing the infiltration and function of CD8 + T cell and macrophage tumor cell phagocytosis in vivo and in vitro .…”
Section: Therapeutic Strategies Targeting Tigit Immune Checkpoint Exp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Azelnidipine is a long-acting third-generation dihydropyridine calcium channel blocker that has been approved for the treatment of hypertension. However, using the molecular operating environment (MOE) by blocking and MST binding assays, molecular docking and structural analysis of CD172a and CD112 have indicated azelnidipine’s potential relevance in cancer immunotherapy ( 171 ). Azelnidipine inhibits the innate checkpoint CD47/CD172a and the adaptive checkpoint TIGIT–CD112 pathways and has anti-cancer effects by increasing the infiltration and function of CD8 + T cell and macrophage tumor cell phagocytosis in vivo and in vitro .…”
Section: Therapeutic Strategies Targeting Tigit Immune Checkpoint Exp...mentioning
confidence: 99%
“…Zhou et al. demonstrated that azelnidipine blocks CD47–CD172a signaling, reactivates macrophage phagocytosis, and improves antitumor immunity even in combination with radiotherapy, as shown in the MC38 murine colon adenocarcinoma cell line ( 171 ). A cancer immunotherapy antibody targeting both CD47 and TIGIT has been patented (WO2020259535).…”
Section: Therapeutic Strategies Targeting Tigit Immune Checkpoint Exp...mentioning
confidence: 99%
“…In the same context, LT3 is of great interest for four additional reasons. First, very recently, Zhou et al suggested that LT3 could be repositioned for cancer immunotherapy based on its ability to block the T Cell Immunoreceptor with Ig and ITIM domains (TIGIT)/poliovirus receptor (PVR) interaction—an emerging immune checkpoint system [ 135 ]. Second, the ability of LT3 to induce phenotypic and functional activation of DCs [ 23 ] could potentiate the promising dendritic cell-based immunotherapy in lung cancer [ 136 ].…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…13 , 97 ), an anti-hypertensive drug approved by the FDA, can be repositioned for cancer immunotherapy by dual blocking CD47/SIRP α and TIGIT/PVR pathways by co-targeting SIRP α and PVR. In vivo , azelnidipine alone or combined with irradiation can significantly inhibits the growth of MC38 tumors and CT26 tumors by enhancing the infiltration and function of CD8 + T cell in tumor 114 . As mentioned above, an increasing number of drugs have been repurposed for cancer immunotherapy, indicating a promising potential on cancer therapy.…”
Section: Molecular Mechanisms Repurposing Non-oncology Drugs In Cance...mentioning
confidence: 99%